CuInS2 sensitized TiO2 for enhanced photodegradation and hydrogen production. Issue 5 (1st April 2019) - Yan, Yujia; Yang, Min; Shi, Huanxian; Wang, Cunjin; Fan, Jun; Liu, Enzhou; Hu, Xiaoyun
Abstract: A novel CuInS2 /TiO2 (CIS-TO) heterojunction which displayed two different transfer pathways of photogeneration carries under UV–vis and Vis light irradiation was fabricated through a facile in-situ growth method. Under vis-light (λ ≥ 420 nm) excitation, 97.37% RhB (10 mg/L) was photodegraded with 20 mg of 1% CIS-TO photocatalyst within 90 min, and the degradation constant could up to 0.0415 min −1, which was about 8.28 times to pure TiO2 (0.00501 min −1 ) and the typical heterojunction was formed between CuInS2 and TiO2 to provide the photo-electrons transfer channel. Under UV–vis light irradiation, a Z-scheme heterojunction was formed to provide another highly effective electron transfer channel for hydrogen production and the hydrogen production rate could reach 785.4 μmol g −1 h −1 with 1% CIS-TO photocatalyst, which showed nearly 1.68 times than that of pure TiO2 . The enhanced photocatalytic activity could be attributed to the synergistic effect of the sensitization and narrow band gap of CuInS2 which could effectively broaden the spectral response range, enhance the photon utilization and inhibit the recombination of photogenerated electrons and holes. Additionally, the high stability of the material was illustrated by the cycle experiments of photodegradation and hydrogen production.